Penerapan Metode Bermain Kotak Geometri dalam Melatih Konsentrasi Anak Usia 5-6 Tahun di TK Aisyiyah Bustanul Athfal 2 Perumnas - Ahmad Farham Majid; Eka Damayanti; Alfia Sri Novendri; A. Sriyanti; St. Naisyah (Faculty of Tarbiyah and Teacher Training, 2023)
The child's concentration ability is very important to be stimulated. One way to stimulate children's concentration is by providing games using geometric squares. This study aims to train concentration in children after the application of the geometric box playing method to children aged 5-6 years. This community service research in the form of service learning was conducted at TK Aisyiyah Bustanul Athfal 2 Perumnas, with 3 children selected as participants based on purposive sampling. The instruments used were geometric squares, observation sheets for children, and intervention implementation evaluation sheets. Data were analyzed using descriptive statistics. The results of the community service research show that children can concentrate on composing geometric shapes according to their shape. The findings in this study imply that children playing with geometric squares benefit because they can increase concentration, can recognize colors, and geometric shapes.